Intrinsic flame-retardant epoxy resin-based composite phase change material and preparation method thereof

By introducing a curing agent for tripolymer thiocyanate graft reaction to generate triazine rings in the phase change material, combined with epoxy resin and phosphate flame retardant, the problem of flammable and leaky phase change material is solved, high flame retardant performance and low leakage rate are achieved, and the thermal management effect of power equipment is improved.

CN120248287AInactive Publication Date: 2025-07-04GUANGDONG UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510409350.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-07-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing phase change materials are flammable and leak-free in power equipment, and cannot meet the flame retardant requirements and long-term use stability. Traditional modification methods cannot solve the compatibility problem between phase change materials and epoxy insulators of power equipment, resulting in a reduction in heat dissipation efficiency.

Method used

Tripolymer thiocyanate grafting reaction is used to generate a curing agent with triazine ring, which is combined with epoxy resin and phosphate flame retardant to form a chemically bonded flame retardant epoxy resin-based composite phase change material, and achieves intrinsic flame retardant and high leakage resistance through innovative molecular structure.

Benefits of technology

It achieves high flame retardant performance and low leakage rate of materials at high temperatures, meets the UL 94V-0 level standard, provides thermal safety and insulation reliability of high-density power equipment, and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248287A_ABST
    Figure CN120248287A_ABST
Patent Text Reader

Abstract

The invention discloses an intrinsic flame-retardant epoxy resin material and a preparation method thereof.The preparation method comprises the steps that an amino curing agent and a molten-state phase-change component are mixed, trithiocyanuric acid is added after uniform stirring, the amino curing agent and the trithiocyanuric acid are subjected to a substitution reaction, a curing agent I with intrinsic flame-retardant characteristics is generated, and the curing agent I with the intrinsic flame-retardant characteristics is obtained; then adding expanded graphite and a melamine and ammonium polyphosphate composite flame retardant, fully mixing, finally adding bisphenol A epoxy resin into the mixture, and carrying out curing reaction to form the intrinsic flame-retardant epoxy resin-based composite phase change material. The intrinsic flame-retardant epoxy resin-based composite phase change material prepared by the preparation method disclosed by the invention has nonflammability and can resist leakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of phase change materials, and particularly relates to an intrinsically flame-retardant epoxy-based composite phase change material and a preparation method thereof. Background Art

[0002] With the rapid development of smart grid and UHV power transmission technologies, the power density and operating temperature of power equipment (such as transformers, GIS switchgear, cable joints, etc.) continue to increase. Research shows that the internal hot spot temperature of power transmission and transformation equipment can reach 130 - 150 °C. Long-term high-temperature operation will double the thermal aging rate of insulating materials (for every 8 - 10 °C increase in temperature, the life is shortened by about 50%), and at the same time, the risk of partial discharge increases significantly (when the temperature rises by 10 °C, the partial discharge amount increases by more than 30%). According to statistics, more than 40% of the faults in the power system are directly related to thermal failure. There is an urgent need to develop efficient thermal management materials to break through the heat dissipation bottleneck of equipment.

[0003] Currently, the thermal management of power equipment mainly relies on forced air cooling or oil circulation cooling technologies. However, such active heat dissipation systems have problems such as high energy consumption (accounting for 5% - 10% of the total power consumption of the equipment), complex structures, and difficulty in adapting to enclosed equipment (such as gas-insulated switchgear). Phase change materials provide a passive and highly reliable thermal control solution for power equipment through the characteristic of absorbing latent heat during solid-liquid phase change. However, traditional paraffin and fatty acid-based phase change materials expose serious applicability defects in the power scenario: firstly, the limiting oxygen index (LOI) of the materials is generally lower than 22%. When an arc fault occurs inside the equipment (local temperature > 3000 °C), it is extremely easy to ignite, which cannot meet the flame retardant requirement of LOI ≥ 28% in the power industry standard GB / T 2408 - 2008; secondly, the phase change materials are prone to leakage from the porous skeleton after multiple thermal cycles (the leakage amount > 5% after 200 cycles). After the liquid component contacts the epoxy insulator of the power equipment, it will cause deterioration of the dielectric properties (the volume resistivity drops by 2 orders of magnitude), seriously threatening the insulation reliability of the equipment.

[0004] Existing improvement technologies mostly adopt physical blending modification methods: for example, encapsulating phase change materials with adsorption carriers such as diatomite and expanded graphite can reduce the leakage rate to 3% - 4%. However, the materials will still slowly leak under the long-term vibration of power equipment (such as magnetostrictive vibration of transformer cores) and thermal stress (annual average leakage amount > 0.8%); at the same time, adding aluminum hydroxide and brominated flame retardants can increase the LOI, but the interfacial bonding force between the flame retardant and the matrix is poor, and it is easy to migrate and precipitate in high-temperature and high-humidity environments. More critically, traditional modification methods cannot solve the compatibility problem between the phase change materials and the epoxy insulators of power equipment. The contact angle between the two is > 90°, and a thermal resistance layer is formed at the interface, resulting in a reduction in the overall heat dissipation efficiency by more than 30%. Summary of the Invention

[0005] In view of the deficiencies in the prior art, the present invention provides an intrinsically flame-retardant epoxy resin-based composite phase change material and a preparation method thereof to solve the technical problems of easy leakage and combustion of phase change materials in power source materials.

[0006] In the first aspect of the present application, a preparation method of an intrinsically flame-retardant epoxy resin-based composite phase change material is provided. The raw materials include epoxy resin with epoxy groups, amine curing agent, trithiocyanuric acid, expanded graphite, phosphoric acid flame retardant and melamine. The preparation method includes the following steps:

[0007] Step 1: Heat and melt the phase change substance. After complete melting, add the amine curing agent and set the temperature to 80 °C, continuously stir for 0.5 - 1.5 hours, then add expanded graphite, phosphoric acid flame retardant and melamine and continuously stir for 1 - 2 h;

[0008] Step 2: Add trithiocyanuric acid to the above mixture and continuously stir until the reaction is complete to form curing agent 1 with a triazine ring;

[0009] Step 3: Add epoxy resin with epoxy groups to the above curing agent 1 with a triazine ring and continuously stir until the reaction is complete, pour it into a mold, and cure and form at room temperature to obtain an intrinsically flame-retardant epoxy resin-based composite phase change material.

[0010] Among them, in Step 1, the heating and melting temperature can be optionally 60 - 80 °C, such as 60, 70, 80 °C, and the stirring speed can be optionally 400 - 800 r / min, such as 400, 500, 600, 700, 800 r / min.

[0011] By fully reacting the molten phase change substance with hydroxyl groups with boric acid and phosphorus pentoxide to generate an amine curing agent, due to the presence of amine groups, trithiocyanuric acid can be grafted, providing a certain flame retardancy and achieving the effect of intrinsic flame retardancy of the material. Then, it undergoes a curing reaction with the epoxy resin glue with epoxy groups to form an effective skeleton of the phase change component. Secondly, the combination with melamine and phosphoric acid flame retardant can improve its flame retardancy to reach V-0; in the traditional method, adding flame retardants through physical mixing will cause problems such as sedimentation and aggregation of flame retardants or uneven distribution of flame retardancy due to multiple phase changes of the material. In this application, through the physical mixing of phosphoric acid flame retardant and melamine plus the incorporation of trithiocyanuric acid, the intrinsic flame retardancy of the phase change material is jointly achieved, so that the flame retardant effect of the material will not decrease due to wear and other reasons; the anti-leakage performance of the phase change material can also be effectively improved through the grafting of trithiocyanuric acid, and the service life of the composite phase change material is prolonged.

[0012] Further, the epoxy resin is any one of the epoxy resins with amine curing agent and epoxy groups.

[0013] Further, the polyethylene glycol is one or more of polyethylene glycol 1500, polyethylene glycol 2000, and polyethylene glycol 4000, so that the phase change material prepared can obtain a high enthalpy value.

[0014] Further, the phosphoric acid flame retardant is any one of ammonium polyphosphate and aluminum hypophosphite.

[0015] Further, the mass ratio of the trithiocyanuric acid to the epoxy resin is (0.25 - 1):1. If the mass ratio of the trithiocyanuric acid to the epoxy resin is too low, it will affect the grafting amount, and further the flame retardant performance of the material cannot meet the requirements. For example, the flame retardant performance of the material cannot reach the V-0 level. In this mass ratio range, the material can be reshaped by external force. Preferably, the mass ratio of the trithiocyanuric acid to the epoxy resin is (0.25 - 1):1, and more preferably 0.5:1.

[0016] The present invention also provides an intrinsically flame-retardant epoxy resin prepared by the preparation method of the epoxy resin.

[0017] In summary, compared with the prior art, the present invention has achieved the following technical effects:

[0018] The intrinsically flame-retardant epoxy resin-based composite phase change material has high anti-leakage performance, high flame retardant performance and reworkability through molecular structure innovation, realizing a leap in the performance of power thermal management materials: on the one hand, the three-dimensional cross-linked network of epoxy resin immobilizes the phase change component through chemical bonding, so that the anti-leakage rate of the phase change component of the material is >99.9% at 150°C, solving the leakage problem of traditional materials; on the other hand, the triazine ring flame retardant groups embedded in the resin matrix can be pyrolyzed into refractory gases at high temperature, so that the material meets the UL 94 V-0 level flame retardant standard, providing an innovative solution with thermal safety, insulation reliability and long life for high-density power equipment. Description of the Drawings

[0019] Figure 1 It is an image of the leakage phenomenon of an intrinsically flame-retardant epoxy resin-based composite phase change material provided in Example 1 of the present invention during continuous heating at 150°C;

[0020] Figure 2 It is the test result of an intrinsically flame-retardant epoxy resin-based composite phase change material provided in Example 1 of the present invention in the vertical burning test; Detailed Embodiments

[0021] To enable those skilled in the art to better understand the solution of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0022] Embodiment

[0023] The present invention will be further described below in conjunction with specific embodiments and comparative examples. The following specific embodiments are all preferred embodiments of the present invention, but the embodiments of the present invention are not limited by the following embodiments, especially not limited to the models of the component raw materials used in the following specific embodiments.

[0024] I. Sources of raw materials for the embodiments and comparative examples

[0025] Unless otherwise specified, the raw material substances used in the embodiments and comparative examples of the present invention are all commercially available.

[0026] II. Test methods for various performances

[0027] (1) Anti-leakage test: The prepared solid-solid phase change material sample is subjected to an anti-leakage test. The test method is as follows: Place the intrinsic flame-retardant epoxy resin-based composite phase change material on a constant-temperature heating table at 150 °C, observe and record the appearance and mass change of the phase change material after continuous heating for 5 h, and calculate the mass retention rate. The calculation formula is as follows: 1 - [(m1 - m2) / m1], where m1 represents the initial mass of the composite phase change material, and m2 represents the mass of the composite phase change material after continuous heating for 5 h. The thermal stability of the phase change material is characterized by the mass change of the composite phase change material in the anti-leakage test.

[0028] (2) Flame retardancy test: Test according to the standard of UL-94-2016;

[0029] The prepared intrinsic flame-retardant epoxy resin-based composite phase change material sample (h = 0.3 mm, d = 10 mm, l = 100 mm) is subjected to a vertical burning test. The test method is as follows: Conduct two ignition tests on the phase change material sample. If it extinguishes within 10 s after the first ignition test and within 30 s after the second ignition test, and there is no burning debris, it is the highest rating V-0 grade.

[0030] Example 1

[0031] Step 1: Pour 55 g of polyethylene glycol 2000 into a magnetic stirring oil bath at 80 °C and heat it to melt. After the polyethylene glycol is completely melted, add 7.5 g of amino curing agent, 2 g of expanded graphite, 8 g of phosphoric acid flame retardant, and 5 g of melamine;

[0032] Step 2: Add 15 g of trithiocyanuric acid to the above mixture and continuously stir at a speed of 800 r / min until the reaction is complete to form a curing agent 1 with a triazine ring;

[0033] Step 3: Add 7.5 g of epoxy resin with epoxy groups to the mixture obtained in Step 2 and continuously stir until the reaction is complete, then pour it into a mold and cure it at room temperature to obtain an intrinsically flame-retardant epoxy resin-based composite phase change material.

[0034] Perform a leakage resistance test on the prepared intrinsically flame-retardant epoxy resin-based composite phase change material to verify whether trithiocyanuric acid is successfully grafted onto the epoxy resin, that is, whether the leakage resistance and flame retardancy are improved. As Figure 1 , it can be seen that the sample of the intrinsically flame-retardant epoxy resin-based composite phase change material has almost no leakage at high temperature, and the mass retention rate is still above 99.9% after continuous heating for 5 h, indicating that the leakage resistance of the phase change material has been greatly improved;

[0035] Perform a flame retardancy test on the material. As Figure 2 , it can be seen that in the vertical burning test of the phase change material sample, it extinguishes after 1 s after the first ignition and extinguishes after 1 s after the second ignition, meeting the UL-94 test V-0 standard, indicating that the flame retardancy of the phase change material has been greatly improved;

[0036] Example 2

[0037] Step 1: Pour 55 g of polyethylene glycol 2000 into a magnetic stirring oil bath at a temperature of 80 °C and heat it to melt. When the polyethylene glycol is completely melted, add 10 g of amino curing agent, 2 g of expanded graphite, 8 g of phosphoric acid flame retardant and 5 g of melamine;

[0038] Step 2: Add 10 g of trithiocyanuric acid to the above mixture and continuously stir at a speed of 900 r / min until the reaction is complete to form a curing agent 1 with a triazine ring;

[0039] Step 3: Add 10 g of epoxy resin with epoxy groups to the mixture obtained in Step 2 and continuously stir until the reaction is complete, then pour it into a mold and cure it at room temperature to obtain an intrinsically flame-retardant epoxy resin-based composite phase change material.

[0040] Example 3

[0041] Step 1: Pour 55 g of polyethylene glycol 2000 into a magnetic stirring oil bath at a temperature of 80 °C and heat it to melt. When the polyethylene glycol is completely melted, add 12.5 g of amino curing agent, 2 g of expanded graphite, 8 g of phosphoric acid flame retardant and 5 g of melamine;

[0042] Step 2: Add 5 g of trithiocyanuric acid to the above mixture and continuously stir at a speed of 700 r / min until the reaction is complete to form curing agent 1 with a triazine ring.

[0043] Step 3: Add 12.5 g of epoxy resin with epoxy groups to the mixture obtained in Step 2 and continuously stir until the reaction is complete, then pour it into a mold and cure it at room temperature to obtain the intrinsically flame-retardant epoxy resin-based composite phase change material.

[0044] Comparative Example 1

[0045] Step 1: Pour 55 g of polyethylene glycol 2000 into a magnetic stirring oil bath at a temperature of 80 °C and heat it until it melts. After the polyethylene glycol is completely melted, add 15 g of amino curing agent.

[0046] Step 2: Add 2 g of expanded graphite, 8 g of phosphoric acid flame retardant, and 5 g of melamine to the above mixture and continuously stir at a speed of 800 r / min until it is evenly mixed.

[0047] Step 3: Add 15 g of epoxy resin with epoxy groups to the mixture obtained in Step 2 and continuously stir for 10 minutes, then pour it into a mold and cure it at room temperature to obtain the epoxy resin-based composite phase change material.

[0048] Table 1 Technical solutions and effects of the examples

[0049] Example 1 Example 2 Example 3 Comparative Example 1 Mass retention rate at 250°C / 5h / % 99.97 99.95 99.93 98.21 Vertical burning test V-0 V-0 V-0 V-1

[0050] In Examples 1-3, epoxy resin with epoxy groups, amino curing agent, trithiocyanuric acid, expanded graphite, phosphoric acid flame retardant, and melamine are all introduced. All the intrinsically flame-retardant epoxy resin-based composite phase change materials prepared in Examples 1-3 can achieve high anti-leakage performance and flame retardancy, realizing the stable use of the phase change material. Comparing Comparative Example 1 with Example 1, in Comparative Example 1, trithiocyanuric acid is not added, and the anti-leakage performance of the epoxy resin-based composite phase change material is significantly deteriorated, and the flame retardancy grade is only V-1 during the flame retardancy test.

[0051] Based on the data description of the mass retention rate at 150 °C / 5 h and vertical burning in Table 1, the intrinsically flame-retardant epoxy resin-based composite phase change materials prepared through Examples 1-3 have obvious advantages compared with the comparative examples and can effectively meet the high standards of customers and the market.

[0052] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A preparation method of an intrinsically flame-retardant epoxy resin-based composite phase change material, characterized in that It includes the following steps: Step 1: Heat and melt polyethylene glycol. After complete melting, add an amine curing agent and set the temperature to 80 °C. Continuously stir for 0.5 - 1.5 hours, then add expanded graphite, a phosphorus-based flame retardant, and melamine and continuously stir for 1 - 2 h; Step 2: Add trithiocyanuric acid to the above mixture and continuously stir until the reaction is complete to form curing agent I with a triazine ring; Step 3: Add an epoxy resin with epoxy groups to the above curing agent I with a triazine ring and continuously stir until the reaction is complete. Pour it into a mold and cure it at room temperature to obtain an intrinsically flame-retardant epoxy resin-based composite phase change material.

2. The preparation method of the epoxy resin according to claim 1, characterized in that, The epoxy resin is selected from bisphenol A epoxy resin.

3. The preparation method of the epoxy resin according to claim 1, characterized in that, The mass ratio of trithiocyanuric acid to epoxy resin is (0.25 - 1):

1.

4. The preparation method of the epoxy resin according to claim 3, wherein The mass ratio of trithiocyanuric acid to epoxy resin is 0.5:

1.

5. The preparation method of the phase change material according to claim 2, characterized in that, The polyethylene glycol is one or more of polyethylene glycol 1500, polyethylene glycol 2000, and polyethylene glycol 4000.

6. The preparation method of the epoxy resin according to claim 1, characterized in that, The phosphorus-based flame retardant is any one of ammonium polyphosphate, aluminum hypophosphite, monoalkyl phosphinate, or aluminum diethyl phosphinate.

7. An intrinsically flame-retardant epoxy resin-based composite phase change material, characterized in that, Prepared by any of the methods of claims 1 - 6.

Citation Information

Patent Citations

  • Flame-retardant composite material and preparation method thereof

    CN118652533A

  • Flame-retardant phase-change material and preparation method thereof

    CN118652534A

  • Intrinsic flame-retardant solid-solid phase change material as well as preparation method and application thereof

    CN119570227A

  • Apparatus for measuring of curvature using artificial intelligence

    KR102442571B1